Metabolic syndrome and its clinical and laboratory indicators in relation to outdoor physical activities: Walking, Nordic walking, and cycling - Sokolova, Juliana; Požarskis, Anatolijs; Požarska, Rita (Edelweiss Applied Science and Technology, 2024)
Aim of the study is to investigate the relationship between outdoor walking and sports activities and the clinical and laboratory indicators of metabolic syndrome. Data for the research were collected through the use of questionnaires, anthropometric measurements, and laboratory tests. Using the National Diabetes Federation guidelines, the data were analyzed to determine whether the respondent had metabolic syndrome. Data analysis was conducted on a sample of 380 patients with metabolic syndrome. The study was conducted through quantitative analysis of cross-sectional data. The descriptive part involved conducting variable frequency and cross-tabulation analysis. Odds ratios were calculated using univariate and multivariate logistic regression models. The odds of increased glycosylated hemoglobin (HbA1c) were 1.8-fold lower in the physically active group than in the non-exercise group (the adjusted odds ratio model for sex, age, and smoking (aOR) = 0.56, 95% confidence interval (CI) 0.34–0.95). The odds of reduced high-density cholesterol (HDL-cholesterol) were three times lower in the physically active group than in the non-exercise group (aOR = 0.29, 95% CI 0.18–0.48). The odds of obesity were 3.7 times lower among patients who exercised than among those who did not (aOR = 0.27, 95% CI 0.10–0.68). Outdoor physical activities have a statistically significant effect on HbA1c levels, HDL-cholesterol, and obesity in patients with metabolic syndrome. Metabolic syndrome patients can be advised to engage in physical activities in order to improve their health.